IMPLEMENTASI PERNYATAAN BERSAMA ANTARA PANITIA URUSAN PIUTANG NEGARA CABANG RIAU DENGAN DEBITUR TERHADAP PENGURUSAN PIUTANG NEGARA DITINJAU DARI HUKUM PERJANJIAN - S.H.,M.H., Wismar Harianto, (Menara Ilmu, 2017)
The State Receivables Committee or abbreviated to PUPN is an InterdepartmentalCommittee responsible for the administration of state receivables that have been submitted toit by Government Agencies or Bodies which are directly or indirectly controlled by the State.As the legal basis of the State Receivables Committee in managing state receivables is LawNo. 49 Prp Year 1960 About the Committee of State Accounts Receivable.Government agencies and State entities that are directly or indirectly controlled by theState, shall submit the handling of the State's bad debts which are and the amounts of whichshall be lawful to the State Receivables Committee. State debt or debt to the State shall be theamount of money which shall be payable to the State or entity, by virtue of any rule, agreementor cause. The administration of State receivables shall be conducted exclusively (not usingprocedures in the HIR / RBG) State Receivables Committee is authorized to take legal steps tosettle the State receivables by final through Joint Statement, Letter of Forcedation andexecution measures on goods of guarantee and or other property Owned by the customer /debt bearer.In the context of dealing with special state receivables (parate executiie) it ismentioned that the handling of state receivables that have been declared stalled, according tothe procedures and authorities set forth in Law No. 49 Prp of 1960, contains elements ofpublic law and therefore In its handling, the State Receivables Committee can not be fullybound to the debt agreement and or claims based on the consideration of civil law, resulting inthe existence of the accounts of that State.In the handling of State receivables, firstly preceded by the delivery of statereceivables from receivables receivables in writing accompanied by the requirements andcompleteness of documents receivable State and after the State Account Receivable Committeeconducted research then by the State Receivables Committee issued a letter ReceiptManagement of State Receivables (SP3N ) And subsequently the State Receivables Committeeshall call the debtor / debtor client, in the event that the debtor arises and acknowledges theamount of his receivables and is willing to settle it, shall be set forth in a Joint Statement, butin the event that the debt insurer does not come to fulfill the call and or not to acknowledgeThe amount of the receivables is then set forth in the Stipulation of the Amount of StateReceivables.Based on Article 10 of Law No. 49 Prp Year 1960. Joint Statement is defined as therecognition of the amount of debt that must be paid by the debtor / debt customers to the Stateon the terms of settlement based on the result of negotiation and agreement between the StateReceivables Committee and the debtor / debt. This Joint Statement is a very important legalfoundation for the State Receivables Committee, because this Joint Statement has the perfectverification power (volledigbewijs) and binding force (dwingendbewijs), therefore this JointStatement is headed for Justice by the One Godhead .Keyword: State Receivables Committee, Joint Statement